Revisiting the OTA-OFC: a systematic review of open fracture classification studies since 2010 - Babapelumi Adejuyigbe, BS; Mohini Gharpure, BS; Ria Tilve, BS; Shravya Kakulamarri, BS; Sophia Wang, BS; Jennifer Kallini, MD; Ashley E. Levack, MD, MAS; Rachel Seymour, PhD; Meir Marmor, MD; The OTA Classifications & Outcomes Committee; Julie Agel, MD; Brett Crist, MD; et al. (OTA International)
Abstract. Introduction:. Management of open extremity fractures presents significant challenges due to infection risks and healing complications. The widely used Gustilo-Anderson classification, established in 1976, categorizes open fractures primarily by wound size. However, it has been criticized for its poor reliability and lack of crucial outcome measures. In 2010, the Orthopaedic Trauma Association open fracture classification (OTA-OFC) was introduced as a more detailed alternative. Despite its reported advantages in reproducibility and predictive ability, the OTA-OFC has not seen widespread clinical adoption. Understanding how the OTA-OFC has been used since its inception may clarify its impact on medical care and the reasons for its slow acceptance. Objective(s):. To assess the usage, benefits, and limitations of the OTA-OFC by a systematic review of all publications that used the OTA-OFC since its inception in 2010. Methods:. Data Sources:. A comprehensive search of Google Scholar, Medline/PubMed, Embase, and Cochrane Database was conducted with the following search terms: [Orthopedic Trauma Association] OR [OTA] AND [Open Fracture Classification] OR [OFC]. Study Selection:. Articles written in English, published between 2010 and 2024, and using the OTA-OFC for research/clinical assessment purposes were included. Data Extraction:. Data were extracted using Covidence. Extracted data included context of OTA-OFC use, benefits and limitations associated with OTA-OFC, and other descriptive information including study design and number of patients. Data Synthesis:. Data were compiled, analyzed, and synthesized using Microsoft Excel. Results/Conclusions:. Although OTA-OFC provides more detailed fracture classification with better outcome predictions, its complexity limits its routine use. Increased clinical evidence and streamlined communication are needed to promote broader acceptance.